The Civil War in Spain, 1936-1939. - Gathered and Annotated By Payne, Robert (New York G. P. Putnam's Sons., 1962)
To mark the 70th anniversary of the Spanish Civil War's outbreak, Antony Beevor has written a completely updated and revised account of one of the most bitter and hard-fought wars of the twentieth century. With new material gleaned from the Russian archives and numerous other sources, this brisk and accessible book (Spain's #1 bestseller for twelve weeks), provides a balanced and penetrating perspective, explaining the tensions that led to this terrible overture to World War II and affording new insights into the war-its causes, course, and consequences.
Includes Index.
Keywords: Civil War (Spain : 1936-1939) -- Spain